2022
DOI: 10.1029/2022gl097945
|View full text |Cite
|
Sign up to set email alerts
|

Burn Severity in Canada's Mountain National Parks: Patterns, Drivers, and Predictions

Abstract: Burn severity refers to the magnitude of fire-induced environmental change, that is, the loss of aboveground and belowground organic matter (Keeley, 2009;Key & Benson, 2006). The term has been used interchangeably with fire severity, but remote sensing applications preferentially use "burn severity" (Keeley, 2009). A comprehensive understanding of burn severity pattern is essential for fire-related ecological research, such as the assessment of post-fire vegetation responses and soil structure changes (e.g.,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 60 publications
1
5
1
Order By: Relevance
“…As reported in different studies, we found that elevation is the topmost variable with significantly higher influence than any other topographic predictors [3], [94], [36]. However, elevation may not be always interpreted independently, because different severity drivers, such as, weather, vegetation composition, fuel availability, moisture, etc.…”
Section: B Influence Of Elevation Slope-aspect and Slope-curvature On...supporting
confidence: 54%
See 4 more Smart Citations
“…As reported in different studies, we found that elevation is the topmost variable with significantly higher influence than any other topographic predictors [3], [94], [36]. However, elevation may not be always interpreted independently, because different severity drivers, such as, weather, vegetation composition, fuel availability, moisture, etc.…”
Section: B Influence Of Elevation Slope-aspect and Slope-curvature On...supporting
confidence: 54%
“…RdNBR is the relative version of Differenced Normalised Burn Ratio (dNBR) calculated as per equation (3), where, dNBR is calculated by differencing Normalised Burn Ratio (NBR) of prefire and postfire images as shown in equation (1). In Landsat images, NBR is given by a band combination of near-infrared (NIR), and shortwave-infrared (SWIR) as shown in equation (2).…”
Section: Methodological Frameworkmentioning
confidence: 99%
See 3 more Smart Citations